The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/16066359.2017.1310205
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of text messaging to assess daily substance use and sexual behaviors among urban emerging adults

Abstract: Participants in this urban, resource-constrained sample found the daily text message methodology acceptable for reporting sensitive information. With rapid advancements in technologies and increased accessibility, text messaging remains a promising methodology for the study of daily processes in substance use and HIV risk behaviors. Keywords: text messaging; assessment; emerging adults; substance use; risky sex; mobile technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…The full protocol and procedures were previously described (Bonar et al, in press; Bonar et al, in press). Research assistants (RAs) recruited during days and evenings, using medical records to identify potential participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full protocol and procedures were previously described (Bonar et al, in press; Bonar et al, in press). Research assistants (RAs) recruited during days and evenings, using medical records to identify potential participants.…”
Section: Methodsmentioning
confidence: 99%
“…They had until midnight to complete each day’s questions that assessed drug use and sexual behaviors for the previous day (Bonar et al, in press). On days when a participant did not report a target behavior (e.g., cannabis use) the survey branched to avoid sending related questions, instead sending an equal number of items querying other activities.…”
Section: Methodsmentioning
confidence: 99%
“…This reflects the generally positive outcomes of studies that have evaluated the feasibility of text messaging and mHealth interventions for HIV prevention and care in other settings. 26,[35][36][37][38][39] Furthermore, initial experience in text message content and platform development, and overall implementation suggests that this method may be a relatively cost-effective tool to support HIV prevention efforts among this risk population, given their widespread use of mobile phones, in contrast to their use of smartphones and internet resources. 23,33,40 Moreover, findings from both quantitative and qualitative responses revealed that participants were generally positive toward text messages, particularly daily PrEP reminders.…”
Section: Discussionmentioning
confidence: 99%
“…For a 90% adherence rate 95% of participants can earn up to $12 over the 30 day study ($13 maximum). Note that this is a fraction of what daily substance use studies normally pay to collect data (e.g., $1-4 dollars per day) [21,77].…”
Section: Other Enhancements To Support Engagementmentioning
confidence: 99%
“…enable better understanding of the real-time antecedents and sequelae of substance use and can inform the development of just-in-time adaptive interventions (e.g., for craving, high-risk activity spaces , negative affect, stress) [19,20,21]. Mobile phones provide a promising platform in this regard.…”
mentioning
confidence: 99%